The Rock Art of Oman 1975 - Clarke, Christopher (The Journal of Oman Studies, 1975)
Keywords: Archéologie – Oman

Survey and Excavations in Central Oman, 1974-75 - Cardi, Beatrice de (Journal of Oman Studies, 1975)
Keywords: Archéologie – Oman

The Incense Port of Moscha (Khor Rori) in Dhofar - Pirenne, Jacqueline (Journal of Oman Studies, 1975)
Keywords: Archéologie – Oman

A possible Link between the Jemdet Nasr and the Umm an-Nar Graves of Oman - Frifelt, Karen (Journal of Oman Studies, 1975)
Keywords: Archéologie – Oman

Oman in the Third Millennium BCE - Hastings, Anne; Humphries, J. H.; Meadows, R.H. (Journal of Oman Studies, 1975)
In the course of two seasons of survey the Harvard Archaeological group has located seventeen settlements which, on the basis of associated ceramics, stone structures, lithic and copper remains, can best be attributed to the Third Millennium BCE. From the accumulated evidence, a preliminary idea of the conditions of life in Bronze Age Oman can be gleaned.
Keywords: Archéologie – Oman

On Prehistoric Settlement and Chronology of the Oman Peninsula - Frifelt, Karen (East and West, 1975)
Keywords: Archéologie – Oman

The archaeology of Oman: a preliminary discussion of the Islamic periods - Whitcome, Donald (Journal of Oman Studies, 1975)
Keywords: Archéologie – Oman